Toward relevant measures of performance to manage complexity in inclusive development projects - Mkhize, Nonhlanhla Patience (Graduate School of Business (GSB), 2022)
The 2030 Agenda on Sustainable Development advocates for innovation for inclusive development. It is a fundamental issue to make progress within South African and globally. When one considers how to improve on the lack of success we have had so far, there are many areas of possible focus. This study looks at the management of innovation for inclusive development projects. These projects are complex. They harness science, technology and innovation to achieve a more inclusive and sustainable society. Their execution remains challenging despite models and tools to manage project complexity. The study focusses on how complexity exerts an influence on the management of these projects. It concurs with the literature that time, cost, and scope are inadequate measures on their own to assess complex project management performance. It seeks relevant measures of performance that can expand the triple constraint model to deal with complexity. To build a theory on the issues of concern, I use the lens of a project as a complex and adaptive temporary organisation. My qualitative study focuses on five projects within the Department of Science and Innovation in South Africa. It collects data from project management personnel, users and sponsors involved in these projects. The informants assist me in understanding the practise and processes of project management organisation and subsequent performance management. The study collects secondary data from various archival records. It uses the Gioia approach to analyse and interpret the data systematically and rigorously. The study contributes to complex project management theory, an evolving field. It expands existing knowledge by demonstrating how complexity influences the organisation of project management. It highlights how the plurality of stakeholders influences the definition and prioritisation of project goals. The prioritisation informs the allocation of resources, a task that is laden with conflict. The stakeholders establish a temporary organisation. The organisation has a unique identity, defined by the collective values of the stakeholders. Its governance is flexible, inclusive and responsive and embraces Ubuntu. Flexibility enhances its response to fluid and unpredictable changes in its context. The study underscores that learning is critical to the continuous improvement of the management of these projects. The stakeholders must recognise different ways of knowing to learn from each other. The findings stress technology appropriateness and its influence on organising project management. Technology itself might be exclusionary and marginalise other stakeholders within the temporary organisation. It shows the link between project management organisation and performance measurement. It highlights how complexity influences the selection of measures of performance. It proposes a four-dimensional model to expand the triple constraint measures. The dimensions are process, scope, context and good governance. The findings recommend further research to 2 understand how complexity influences the management of innovation for inclusive development projects.